2014
DOI: 10.1186/1743-0003-11-58
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of gait patterns in vestibular neuritis patients using gyroscope sensor and a continuous walking protocol

Abstract: BackgroundLocomotion involves an integration of vision, proprioception, and vestibular information. The parieto-insular vestibular cortex is known to affect the supra-spinal rhythm generators, and the vestibular system regulates anti-gravity muscle tone of the lower leg in the same side to maintain an upright posture through the extra-pyramidal track. To demonstrate the relationship between locomotion and vestibular function, we evaluated the differences in gait patterns between vestibular neuritis (VN) patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…When there is damage to these vestibular organs and subsequent loss of sensory input during motion, normal gait patterns are compromised [6]. Recent studies have shown a link between vestibular impairment and gait abnormalities in patients with vestibular disorders such as vestibular neuritis and vestibular schwannoma, including decreased gait speed and increased variability in stance and swing time [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…When there is damage to these vestibular organs and subsequent loss of sensory input during motion, normal gait patterns are compromised [6]. Recent studies have shown a link between vestibular impairment and gait abnormalities in patients with vestibular disorders such as vestibular neuritis and vestibular schwannoma, including decreased gait speed and increased variability in stance and swing time [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians and scientists have been calling for a portable, reliable, low-cost, and time-saving gait analysis system for decades. In recent years, wearable sensors like accelerometers and gyroscopes have enabled us to record spatial temporal, kinematic and kinetic data, and to analyze the gait outside conventional gait laboratories 14,[18][19][20][21] , including the quantification of gait and movement disorders 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Walking stability during natural walking have been used to quantify the balance ability and disease severity, which can be accessed using wearable sensors without the limitations of a gait laboratory environment [11][12][13]. The sensor-based measurements of walking stability include root mean square (RMS), harmonic ratio (HR), gait variability, gait symmetry and gait regularity [14].…”
Section: Introductionmentioning
confidence: 99%